Main causes of homelessness and adaptation of homeless to environmental factors - Sarnowska, Marta; Gach, Sonia (Journal of Education, Health and Sport, 2018)
The problem of homelessness occurs in every country in the world, regardless of the type of governance, economic situation or cultural tradition. At the turn of the 1980s, there were socio-economic changes in Poland and the marketization of the economy, which resulted in the collapse of the economy and the liquidation of a number of enterprises, resulting in numerous redundancies. In addition, there were changes to the housing law, which involved the possibility of eviction. As a result of the above changes, i.e. the loss of permanent work and subsequent threats of evictions from rented premises and the inability to deal with the new economic situation, a homeless group was formed. The aim of the field research, at a randomly selected group of 10 homeless people, was to assess the quality of life of these people. This group did not have a permanent place of residence and did not use shelters, night shelters or social care homes. The research was carried in the city of Wrocław, Duszniki Zdrój, Kłodzko and the Szczytna commune. The study group was in the 35-71 age range, the research was carried out on the terrain, ie the natural environment of individual subjects. The examined persons had vocational and basic education. The study contains the results of qualitative research based on the well-grounded theory, thanks to which the hypotheses were created during the research, which allowed for in-depth analysis of the conducted conversations and observations as well as participant observation. The results of the study showed that 7 homeless people indicate dependence on the previous system for the main cause of homelessness. Along with political and economic changes, they lost their jobs and shelter (they lived in the State Farms and workers' hotels). This is not the only cause, but the most accented. They also show great adaptability in relation to environmental, housing and nutritional conditions, showing resistance to both infectious and systemic diseases.